Pengaruh Sistem Perpajakan, Pemeriksaan Pajak, Dan Sanksi Pajak, Terhadap Penggelapan Pajak - Ahmad Rusli Hidayat Almasuri; Eva Herianti (CV. ITTC INDONESIA, 2026)
Tax evasion has consistently been a subject of academic research in both developed and developing countries for many years. Discussions and studies on this issue continue to evolve in line with efforts to find effective solutions to address tax evasion. This study aims to identify the factors that influence tax evasion, particularly the tax system, tax audits, and tax sanctions among MSMEs located in Pasar Pagi Mangga Dua, North Jakarta. The research employs a quantitative approach with a population consisting of MSMEs operating in Pasar Pagi Mangga Dua, North Jakarta. The sampling technique used is non-probability sampling with a purposive sampling method, resulting in a total of 67 samples. Data analysis was conducted using outer model and inner model analysis, as well as hypothesis testing with the help of the SMART-PLS Version 4 software. The results of the study indicate that the tax system, tax audits, and tax sanctions have an influence on tax evasion. These findings suggest that a wellstructured tax system, intensive audits, and sufficiently strict sanctions can reduce tax evasion and, in turn, increase state revenue.